Screening for depression in chronic haemodialysis patients as a part of care in dialysis setting: a cross-sectional study - Kubanek, Alicja; Renke, Marcin; Godlewska, Beata R.; Paul, Przemysław; Przybylak, Mateusz; Kowalska, Anna S.; Wąż, Piotr; Błaszczyk, Michał; Macul-Sanewska, Aleksandra; Rutkowski, Przemysław; Czarnacka, Kamila; Bednarski, Krzysztof; et al. (Frontiers in Psychiatry, 2024)
Dear Editors, Our study concerns depressive disorders in hemodialysis patients. It suggests that the regular screening for depressive symptoms, followed by a psychiatric consultation in selected patients, might improve diagnosing depression with the goal of achieving a higher quality of life and a lower mortality rate. It may also be a cost-effective model for the management of depression among the hemodialysis population. It seems to be consistent with the scope of Your Journal, focused on improving therapeutic options for mental illness and consequently to improve patient treatment outcomes.